Stretch marks, causes and treatments used today – Scoping review - Cardoso, Andressa Silva; Braga, Cristina; Menezes, João Carlos de Andrade; Ocon, Carlos Alberto; Lazzareschi, Leandro; da Cunha, Márcio Fernandes; Fernandes, Antônio de Olival; Filoni, Eduardo (Seven Editora, 2024)
Introduction: As it is the largest organ in the body, the skin is more exposed to solar radiation, body changes as well as genetics. The skin covers the body and acts as a physical barrier between the body and the outside environment and represents about 16% of body weight. Because the skin is an organ with numerous functions, it is exposed to structural changes that are easily perceived by the naked eye, including stretch marks. For a better understanding, we need to understand that the elastic fibers of the skin are the starting point for the formation of stretch marks. Methodology: This is a scoping review where descriptors in Health Sciences - DeCS were used. The descriptors of interest and Boolean operators were: "Therapeutic AND "Skin Lesions (stretch marks)". The search was carried out in the PubMed, Scielo and Bireme databases by these databases provide a broad search combining information from other platforms, using 19 relevant articles. Results: There are treatments that can treat and reduce this problem and include micropuncture, microdermabrasion, microneedling, carboxytherapy as well as the combination of treatments, which must be performed by trained professionals due to their specificities. Final considerations: Stretch marks are acquired integumentary lesions and, like any scar, can be considered a difficult treatment. However, with the current advancement of techniques, there are several aesthetic treatments that are performed, however, there is no scientific proof of their effectiveness for the total disappearance of stretch marks and, as it is a genetic predisposition, prevention includes both the maintenance of the ideal weight and good skin hydration. DOI:https://doi.org/10.56238/sevened2024.025-026